Administrative and Pharmaceutical Screening of Prescriptions Served at Pharmacies X and Y, Banyuwangi Regency - Stephanie Devi Artemisia; Dita Amanda Deviani; Titis Sriyanti; Anung Kustriyani; Sari Prayudeni; Rico Aji Syahputra; Sindi Fatma Fahela (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Prescription screening remains a problem, both at the administrative, pharmaceutical, and clinical levels. Prescription screening is one aspect that can prevent medication errors. Medication errors can occur due to unclear or missing information regarding the route of administration, dosage, frequency of administration, dosage form, patient identity, and prescriber identity. Methods: The research was a descriptive, non-experimental study with retrospective data at Pharmacies X and Y. The number of samples was determined by calculating the number of prescription populations received and taken randomly. 240 prescription sheets were used from Pharmacy X and 94 sheets at Pharmacy Y. The prescription sheets were subjected to administrative and pharmaceutical screening and analyzed. Results: The completeness of prescriptions administratively for Pharmacy X was 60.67% and Pharmacy Y was 69.04%. Administrative screening that was often incomplete was the completeness of prescriptions related to body weight, only 2.08% for Pharmacy X and 0% for Pharmacy Y. The physician's initials or signature also had a completeness of prescriptions of 11.67% for Pharmacy X and 25.53% for Pharmacy Y. Pharmaceutical screening in general was 81.82% for Pharmacy X and 93.44% for Pharmacy Y. Incomplete pharmaceutical screening in both pharmacies was drug strength, namely 50.83% at Pharmacy X and 31.91% at Pharmacy Y. At Pharmacy X, incomplete prescriptions were also found in the writing of dosage forms of 52.03%. Conclusions: The administrative and pharmaceutical completeness of prescriptions from both pharmacies still does not meet the standards of pharmaceutical services in pharmacies.